Research handbook on human rights and investment - Radi, Yannick (Research handbooks in international law, 2018)
In today's globalised world, the relationship between human rights and investment is an important societal and legal issue. This Research Handbook unravels this complex interaction and sheds light on all of its dimensions; it takes stock of the impact that investment operations can have on human rights and it examines how international law addresses, and contributes to, this complicated interplay. Taking a unique approach, this Research Handbook contains insightful chapters that provide analyses of specific international law regimes, with a particular focus on international investment law and arbitration. It also offers in-depth discussions of the corporate and home state responsibilities that can result from the activities of multinational corporations. Sectorial and regional case studies are also explored; they provide a grounding for the more theoretical aspects of the Research Handbook and highlight the key sectors, such as the agricultural and extractive industries, that are prone to human rights violations. Academics, students, practitioners and policy-makers, with an interest in human rights law, international economic law and the activities of multinational corporations, will find this Research Handbook to be an important resource in their daily research and practice.